Coccidiosis in village chicken: a preliminary survey in Pasir Putih District, Kelantan, West Malaysia - Norlida O. (2020)
A study was carried out to detect and identify the presence of coccidia oocysts in the faeces of village chicken from the district of Pasir Putih, Kelantan, West Malaysia. A total of 135 fecal samples were collected from 15 areas in the Pasir Putih District. The faecal samples were examined by direct smear method (qualitative study). A pinch of the faeces was put onto the glass slide with 1-2 drops of normal saline and cover slip, which was then observed under the compound microscope to detect the coccidia oocysts. The presence of coccidia oocyst was then identified by its size and shape. Results showed that ten out of 135 samples were positive for coccidia oocysts, and classified as Eimeria maxima and Eimeria mitis, both of which are from two locations at Kampung Chap Banir, Pasir Putih, Kelantan. The remaining 125 samples were observed to be negative. This may suggest that the chickens reared in the backyard (extensive) are less susceptible to the coccidia infection due to their environment with lower stocking density (mostly free ranging chicken), and no damp/wet litter as bedding which can facilitate sporulation of the coccicia oocyst thereby spreading the infection. Further studies need to be done to elucididate other factors which may affect coccidial infections in free range chicken such as the availability of medications in feed or genetic hardiness and tolerance to field infections. The local village chicken industry is an up and coming facet of the poultry industry and needs concerted efforts to boost it.